Mapping the Landscape of Women Entrepreneurship: A Bibliometric Analysis - Lama, Padam Bahadur; Budhathoki, Prem Bahadur; Chataut, Mukund Kumar (The International Research Journal of Management Science, 2025)
Background: Women entrepreneurship plays a vital role in economic growth and job creation, highlighting the importance of understanding its landscape. Objectives: The study aims to evaluate trends and advancements in women entrepreneurship research discovering future research direction. Method: This study analyzed Scopus data of 5992 covering from 2001 to 2023 and utilized R Biblioshiny and VOS viewers. Results: The findings show increasing trends in women's entrepreneurship. USA and UK significantly contributed, identifying the International Journal of Entrepreneurship, and Entrepreneurship and Regional Development as pertinent sources. Likewise, the most frequently mentioned authors were Hoang and Antonicic, with the predominant term being entrepreneurship. Conclusion: The study tracks the increasing trends of women entrepreneurship enhancing contribution to existing literature and depict the direction of the research. Implication: This study shows women's entrepreneurship's growing popularity and its contributors. Further, the study shows gaps, rising trends, and other important landscapes for academician and policymakers.